PENGARUH PROSES PENGADUKAN TERHADAP KARAKTER ADONAN DAN SIFAT BIODEGRADABLE PLASTIC YANG DIBUAT DARI BUNGKIL BIJI JARAK PAGAR - Hari Arbiantara; Mahros Darsin; Triana Lindriati (Jurusan Teknik Mesin Fakultas Teknik Universitas Jember, 2013)
Manufacture of biodegradable plastics in this study begins with making the dough using a single screw extruder, then the dough is molded by using a compression molding machine. The basic material used is a mixture of jatropha seed meal, corn starch, CMC (composition 7: 2: 1). This study aimed to study the effect of Helic corner and screw compression ratio of the batter character and biodegradable plastic produced. Helic screw angle was varied from 2,5o; 5o; 7.5 ° and screw compression ratio varied from 1.5; 2.5; 3.5. The results showed an increase in the angle of screw Helic simplify the process of molding (lowering the value of Tg, Tm, ΔH and texture of the dough) and to improve the mechanical physical properties of the biodegradable plastic produced (tensile strength, strain increases while the thickness and Water Vapor transmition rate decreases). Improved compression ratio increase and decrease the thermal properties of dough texture and increase the tensile strength and strain, decrease the thickness and Water Vapor transmition rate of biodegradable plastic produced. Keyword: biodegradable plastic, mold, helical degree, compression ratio